PERANCANGAN DATA WAREHOUSE DAN PENERAPAN ALGORITMA ID3 PADA ANALISA POTENSI DAN HAMBATAN PERKEMBANGAN DESA BERDASARKAN POLA HIDUP MASYARAKAT - Sehman Sehman (Jurnal Teknika, 2019)
The lack of understanding of the importance of data will result in a large impact loss because with the existence of an important sense of the data, an agency either private or public company will easily make decisions. A data warehouse is an option that must be considered for the village in processing and storing large classified data such as data from a village. In addition to the application of the research data warehouse, it also uses the ID3 algorithm which is useful as a theory to analyze the potentials and obstacles that affect the development of a village based on the data of the lifestyle of the local community. Data on population, education, health, conditions of infrastructure, village finance, village assets, community organizations, community economic activities and daily activities of the village community will be extracted and stored by building a data warehouse, data is sought from data warehouse which will be used as dataset pattern community life so that it is easily analyzed and can be used as training data to make decisions by applying the ID3 algorithm. The ID3 algorithm that has been applied to the community lifestyle dataset will produce a rule that has an influential potential class, and the potential to hamper village development. The accuracy of the system to be made has a hypothesis of 95%. because the rule generated by id3 will be compared with the rule collected based on respondents from the previous data, which is data on urban residents who have advanced.